Significance of anti-cyclic citrullinated peptide autoantibodies in immune-mediated inflammatory skin disorders with and without arthritis - Chander Grover; Bineeta Kashyap; Deepashree Daulatabad; Amit Dhawan; Iqbal R Kaur (Wolters Kluwer Medknow Publications, 2016)
Background: Anti-cyclic citrullinated peptides (CCPs) are autoantibodies directed against citrullinated peptides. Rheumatoid factor (RF), an antibody against the Fc portion of IgG, is known to form immune complexes and contribute to the etiopathogenesis of various skin disorders. C-reactive protein (CRP), an acute-phase protein, increases following secretion of interleukin-6 from macrophages and T cells. Anti-CCP, RF, and CRP are well-established immune-markers, their diagnostic potential in immune-mediated skin disorders remains less widely studied. Aims and Objectives: To determine the correlation between anti-CCP, RF, and CRP in immune-mediated inflammatory skin diseases. Materials and Methods: About 61 clinically diagnosed cases of various immune-mediated skin diseases (psoriasis [n = 38], connective tissue diseases such as systemic lupus erythematosus and systemic sclerosis [n = 14], and immunobullous disorders including pemphigus vulgaris and pemphigus foliaceus [n = 9]) were included in the study. These patients were subclassified on the basis of presence or absence of arthritis. Arthritis was present in nine cases of psoriasis and seven connective tissue disorder patients. Detection of serum anti-CCP was done using enzyme-linked immunosorbent assay, whereas CRP and RF levels were detected using latex agglutination technique. Results: Of the 61 specimens, 14.75% had elevated serum anti-CCP levels. RF and CRP levels were elevated in 18.03% and 39.34% specimens, respectively. RF was elevated in 13.16% of inflammatory and 42.88% of connective tissue disorders, whereas anti-CCP was raised in 10.53% of inflammatory and 35.71% of connective tissue disorders. CRP positivity was highest in connective tissue disorders (50%), followed by 39.47% in inflammatory and 22.22% in immunobullous conditions. In none of the immunobullous patients, anti-CCP or RF levels were found to be elevated. Association of the presence of arthritis with elevated anti-CCP was found to be statistically significant. Conclusions: Although anti-CCP, RF, and CRP levels are valuable markers of chronic immune-mediated skin disorders, elaborate studies enrolling a larger number of patients are required to validate these diagnostic markers.